2017
DOI: 10.4067/s0718-95162017000400011
|View full text |Cite
|
Sign up to set email alerts
|

Functional land-use change effects on soil fungal communities in Chilean temperate rainforests

Abstract: By reducing soil organic matter and litter input, land-use changes are predicted to decrease total soil fungal diversity, but at functional levels this have been poorly studied. It is expected, though, that increasing disturbance decreases saprotrophic and mycorrhizal fungi biodiversity. This study aimed to determine the effects of land-use changes on the phylogenetic and functional diversity of soil fungi in the Southern Andes. We assessed the fungal communities of Andosol topsoil at 1 cm and 10 cm soil depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…The most abundant classes in both seasons were the Agaricomycetes, followed by Leotiomycetes, Sordariomycetes, and Tremellomycetes. These results could partially overlap with the work of Marín et al (2017) and Duo Saito et al (2018). Marín et al (2017) found that in general Agaricomycetes, Dothideomycetes, and Sordariomycetes were the most abundant soil fungus classes in Nothofagus forests of Chile.…”
Section: Tablementioning
confidence: 61%
See 4 more Smart Citations
“…The most abundant classes in both seasons were the Agaricomycetes, followed by Leotiomycetes, Sordariomycetes, and Tremellomycetes. These results could partially overlap with the work of Marín et al (2017) and Duo Saito et al (2018). Marín et al (2017) found that in general Agaricomycetes, Dothideomycetes, and Sordariomycetes were the most abundant soil fungus classes in Nothofagus forests of Chile.…”
Section: Tablementioning
confidence: 61%
“…These results could partially overlap with the work of Marín et al (2017) and Duo Saito et al (2018). Marín et al (2017) found that in general Agaricomycetes, Dothideomycetes, and Sordariomycetes were the most abundant soil fungus classes in Nothofagus forests of Chile. Furthermore, Duo Saito et al (2018) found that in naked soil near glaciers the Leotiomycetes were the most common taxon, followed by Sordariomycetes, Dothideomycetes, and Eurotiomycetes.…”
Section: Tablementioning
confidence: 61%
See 3 more Smart Citations